A novel core-shell denitrification catalyst and its synthesis method and application
By designing a new core-shell Cu-SSZ-13 denitrification catalyst, the existing catalysts have been solved, and the problems of insufficient activity in the low-temperature segment, poor selectivity in the high-temperature segment and low hydrothermal stability are achieved, and efficient NOx conversion and excellent hydrothermal stability are achieved in a wide temperature range.
Patent Information
- Application Number
- CN202411982188.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The existing Cu-SSZ-13 molecular sieve catalysts have insufficient catalytic activity in the low-temperature stage, poor ammonia nitrogen reduction selectivity in the high-temperature stage, and low stability in resistance to hydrothermal aging.
The new core-shell Cu-SSZ-13 denitrification catalyst is used, which has a low core silicon-aluminum ratio, a high copper load, a high silicon-aluminum ratio, and a low copper load. Copper is supported by solution ion exchange method to form a core-shell copper-based SCR catalyst with high internal loading inside and low external loading.
Maintain high catalytic activity in the low-temperature stage, high denitrification performance in the high-temperature stage, and significantly improve the resistance to hydrothermal aging, which is suitable for the purification of NOx in diesel vehicle exhaust.
Smart Images

Figure CN119771489A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of denitration catalysts, and in particular relates to a novel core-shell denitration catalyst and a synthesis method and application thereof. Background Art
[0002] At present, ammonia (NH3) is used as a reducing agent to reduce nitrogen oxides (NO x ) is catalytically reduced to harmless N2 and H2O under the action of a catalyst, namely the NH3-SCR method, which is the most promising method for the application of nitrogen oxides (NO x ) elimination technology, the core of which is the SCR catalyst.
[0003] In recent years, SCR denitration catalysts prepared by transition metal / rare earth metal doped SSZ-13, ZSM-5 or Beta molecular sieves have attracted wide attention due to their excellent catalytic activity and environmental friendliness, such as Cu-SSZ-13, Cu-ZSM-5, Fe-ZSM-5, Cu-Beta, Cu / Ce-SSZ-13, Fe / Ce-Beta, etc. Among them, the research on small pore molecular sieve SSZ-13 has attracted more and more attention. Compared with Cu-ZSM-5 and Cu-Beta, Cu-SSZ-13 shows better denitration catalytic activity and N2 selectivity.
[0004] However, the existing Cu-SSZ-13 molecular sieve still has the problems of insufficient low-temperature catalytic activity, poor high-temperature ammonia nitrogen reduction selectivity, and low hydrothermal aging stability. Specifically, the Cu-SSZ-13 molecular sieve catalyst with high copper loading (>3.0wt%) has excellent denitrification performance in the low-temperature range. However, literature research shows (ACS Catal.2017,7,8214-8227) that in the high-temperature range, the active species Cu is prone to agglomeration to form CuO x Clusters, reducing agent NH3 in CuO x The clusters are more likely to react with O2 and be oxidized into N2 and H2O, resulting in NO x The conversion rate is greatly reduced and the denitrification performance is not ideal; if the copper loading is low, the denitrification performance in the low temperature section cannot be guaranteed. Summary of the invention
[0005] Based on the above technical problems, the present invention provides a new core-shell Cu-SSZ-13 denitration catalyst, wherein the core has a low silicon-aluminum ratio and a high copper loading, and the shell has a high silicon-aluminum ratio and a low copper loading. The denitration catalyst not only has high low-temperature catalytic activity, but also has high denitration performance at high temperatures and excellent resistance to hydrothermal aging.
[0006] The technical solution of the present invention is specifically as follows:
[0007] The invention provides a novel core-shell denitration catalyst. The novel core-shell denitration catalyst is a Cu-SSZ-13@Cu-SSZ-13 molecular sieve with a Cu loading of 3.5wt%-4.5wt% and a silicon-aluminum ratio of 4-10 as a core phase and a Cu-SSZ-13 molecular sieve with a Cu loading of 1.5wt%-3wt% and a silicon-aluminum ratio of 13-17 as a shell phase.
[0008] The present invention also provides a method for synthesizing a novel core-shell denitration catalyst, comprising the following steps: preparing a Na-SSZ-13@Na-SSZ-13 molecular sieve by an ion exchange method, wherein the Na-SSZ-13@Na-SSZ-13 molecular sieve has a core-shell structure, a core-phase silicon-aluminum ratio of 4-10, and a shell-phase silicon-aluminum ratio of 13-17.
[0009] The synthesis method of the present invention first prepares a Na-SSZ-13@Na-SSZ-13 molecular sieve, wherein the Na-SSZ-13@Na-SSZ-13 molecular sieve has a low silicon-aluminum ratio in the core phase and a high silicon-aluminum ratio in the shell phase, and then copper is loaded by a solution ion exchange method. Since the silicon-aluminum ratio of the molecular sieves in the inner core and the outer shell is quite different, the low silicon-aluminum ratio molecular sieve has a high theoretical negative copper amount, and the high silicon-aluminum ratio molecular sieve has a low theoretical negative copper amount, and finally a core-shell type copper-based SCR catalyst with a high copper loading inside and a low copper loading outside is formed.
[0010] Preferably, the preparation method of Na-SSZ-13@Na-SSZ-13 molecular sieve includes: S1, preparing a low silicon-aluminum ratio SSZ-13 molecular sieve inner core by a rotation crystal method; S2, synthesizing a high silicon-aluminum ratio SSZ-13 molecular sieve outer shell by a hydrothermal method; S3, preparing a core-shell structured supported catalyst, using a low silicon-aluminum ratio SSZ-13 molecular sieve as the core phase, and then performing surface functionalization treatment on the core phase molecular sieve, and growing a layer of high silicon-aluminum ratio SSZ-13 on its surface as the shell phase, thereby obtaining Na-SSZ-13@Na-SSZ-13 molecular sieve.
[0011] Preferably, the specific process of the ion exchange is: adding Na-SSZ-13@Na-SSZ-13 molecular sieve to ammonium sulfate solution for ion exchange to obtain H-SSZ-13@H-SSZ-13 molecular sieve; then placing the H-SSZ-13@H-SSZ-13 molecular sieve in a copper acetate solution for ion exchange to obtain Cu-SSZ-13@Cu-SSZ-13 molecular sieve; the mass volume ratio (g / mL) of the Na-SSZ-13@Na-SSZ-13 molecular sieve to the ammonium sulfate solution and the copper acetate solution is 1:5-15:3-8; preferably, the concentration of the ammonium sulfate solution is 0.4-0.6 mol / L; the concentration of the copper acetate solution is 0.1-0.3 mol / L.
[0012] Preferably, the temperature for ion exchange in ammonium sulfate solution is 75-85° C., the exchange time is 5-7 hours, and the number of exchanges is 3-4 times; the temperature for ion exchange in copper acetate solution is 75-85° C., and the exchange time is 5-7 hours.
[0013] Preferably, the synthesis method of the Na-SSZ-13@Na-SSZ-13 molecular sieve is: (1) using a crystal rotation method to synthesize a core phase Na-SSZ-13 molecular sieve with a silicon-aluminum ratio of 4-10; (2) adding the core phase Na-SSZ-13 molecular sieve to the initial mother liquor of SSZ-13 molecular sieve synthesis, stirring, and crystallizing to generate a shell phase Na-SSZ-13 molecular sieve with a silicon-aluminum ratio of 13-17 on the core phase Na-SSZ-13 molecular sieve.
[0014] Preferably, the specific process of step (1) is: mixing the alkali source, silicon source, water, template and aluminum source in a molar ratio of 0.1-0.3:1:5.0-15.0:0.01-0.05:0.02-0.08, and stirring evenly to obtain an initial gel; placing the initial gel in a high-temperature reactor, crystallizing at 120-160°C for 8-24h, cooling, separating, drying and calcining to obtain a core phase Na-SSZ-13 molecular sieve with a silicon-aluminum ratio of 4-10; preferably, the crystallization reaction temperature is 140-160°C; preferably, the crystallization reaction time is 12-18h.
[0015] Preferably, in step (1), the alkali source is selected from NaOH or KOH; the silicon source is selected from one or a combination of water glass, tetraethyl orthosilicate, silica sol, fumed silica, sodium silicate; the template is N,N,N-trimethyl-1-adamantanammonium hydroxide; and the aluminum source is Y molecular sieve.
[0016] Preferably, the Y molecular sieve is selected from one or a combination of NaY, NH4Y, HY; the silicon-aluminum ratio of the Y molecular sieve is 1-20; preferably, the Y molecular sieve is NaY; preferably, the silicon-aluminum ratio of the Y molecular sieve is 2-10; more preferably 5-7.
[0017] Preferably, the specific process of step (2) is: mixing the SSZ-13 molecular sieve synthesis initial mother liquor composed of an alkali source, a silicon source, water, a template agent, and an aluminum source in a molar ratio of 0.05-0.1:1:8.0-20.0:0.01-0.05:0.05-0.1 with the core phase Na-SSZ-13 molecular sieve having a silicon-aluminum ratio of 4-10 obtained in step (1), stirring, crystallizing at 150-170° C. for 18-26 hours, cooling, separating, drying, and calcining to obtain Na-SSZ-13@Na-SSZ-13 molecular sieve;
[0018] Preferably, the alkali source is selected from NaOH or KOH; the silicon source is selected from one or a combination of tetraethyl orthosilicate, silica sol, fumed silica, sodium silicate; the template is N,N,N-trimethyl-1-adamantanammonium hydroxide; and the aluminum source is aluminum sulfate.
[0019] The present invention also provides the application of the novel core-shell denitrification catalyst as an NH3-SCR catalyst, and the specific application conditions are: the reaction temperature is controlled at 120-650°C, NH3 is used as the reducing agent, the gas flow rate is 500ml / min, and the space velocity is 80000-200000 / h; preferably, the catalyst is first subjected to hydrothermal aging treatment and then used for catalytic reduction of NOx, and the treatment conditions are: at 850°C, treated in air containing 10% water vapor for 16 hours.
[0020] Beneficial effects of the present invention:
[0021] The catalyst of the present invention is a novel core-shell denitration catalyst with a Cu-SSZ-13 molecular sieve with a low silicon-aluminum ratio and a high copper load as a core phase and a Cu-SSZ-13 molecular sieve with a high silicon-aluminum ratio and a low copper load as a shell phase. By designing the catalyst structure, silicon-aluminum ratio, and copper load, in the low temperature section, NH3 and NO participating in the reaction can enter the Cu-SSZ-13 catalyst body with a low silicon-aluminum ratio and a high copper load in the inner core in time due to the absence of mass transfer diffusion restriction, so that NO is efficiently selectively catalytically reduced to N2 and H2O; in the high temperature section, the mass transfer diffusion restriction of NH3 and NO at high temperature is utilized, so that the NH3 and NO participating in the reaction can react with the Cu active sites on the surface when they just reach the outer shell of the Cu-SSZ-13 catalyst with a high silicon-aluminum ratio and a low copper load, so as to reduce NO, and cannot quickly diffuse into the inner core with a high copper load. In this way, when the catalyst is used for SCR denitrification reaction, it can ensure that the catalyst has high catalytic activity in the low temperature section, while avoiding the oxidation of NH3 by O2 in the high temperature section, which leads to a decrease in NO conversion efficiency, solves the problem of a sharp drop in SCR catalyst performance in the high temperature section, ensures that the catalyst also has high denitrification performance in the high temperature section, and its resistance to hydrothermal aging is also improved.
[0022] Specifically: the catalyst has a wide temperature window and has excellent catalytic activity in the temperature range of 180℃-650℃ (NO x Conversion rate>90%); for hydrothermal stability, after aging at 850°C and 10% water vapor for 16 hours, the catalyst still maintains a conversion rate of more than 80% in the range of 180°C-650°C, and is suitable for the purification of NOx in diesel vehicle exhaust to meet the "National VI" exhaust emission standards. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1XRD diagrams of samples of Examples 1, 2, 3, 4 and Comparative Examples 1 and 2;
[0024] Figure 2 The SEM images of samples of Examples 1, 2, 3, 4 and Comparative Examples 1 and 2 are shown;
[0025] Figure 3 The catalytic performance comparison diagram of the aged samples of Examples 1, 2, 3, 4 and Comparative Examples 1 and 2 is shown; DETAILED DESCRIPTION
[0026] The technical solutions of the present invention are described in detail below through specific embodiments. However, it should be clearly stated that these embodiments are for illustration only and are not to be construed as limiting the scope of the present invention.
[0027] Example 1
[0028] A novel core-shell denitration catalyst, comprising a Cu-SSZ-13 molecular sieve with a Cu loading of 4.0wt% and a silicon-aluminum ratio of 8 as a core phase, and a Cu-SSZ-13 molecular sieve with a Cu loading of 2.0wt% and a silicon-aluminum ratio of 17 as a shell phase, namely, Cu-SSZ-13@Cu-SSZ-13 molecular sieve.
[0029] The synthesis method of the novel core-shell denitration catalyst is as follows:
[0030] Mix 5.678g NaOH and 22g deionized water, put them into a crystallization kettle, stir at 60 rpm at room temperature to obtain a clear solution, then add 35ml water glass with a modulus of 3.0 (containing 28.5% SiO2 and 9.5wt% Na2O), 9.0ml TMAdaOH aqueous solution with a mass fraction of 25wt% and 50g deionized water, and finally add 5.0g NaY molecular sieve. Seal the kettle, heat to 140℃, and continue stirring for crystallization for 12h. After the reaction is completed, cool down and release the pressure. After filtering and washing the product, place it in a 120℃ oven to dry for 6h, and then roast it in a 550℃ muffle furnace for 8h. Finally, Na-SSZ-13 with a SiO2 / Al2O3 ratio of 8 is obtained.
[0031] 35.0ml silica sol (containing 30.1% SiO2), 1.22g NaOH, 12.18g aluminum sulfate (containing 15.9wt% Al2O3), 5.0g TMAdaOH, 8.0g Na-SSZ-13 with a SiO2 / Al2O3 ratio of 8 synthesized in the previous step and 40g deionized water were added in sequence. Seal the kettle, heat to 160°C, and stir continuously for 24h. After the reaction is completed, cool down and release the pressure. After filtering and washing the product, place it in a 100°C oven to dry for 8h, and then roast it in a 600°C muffle furnace for 6h. Finally, Na-SSZ-13@Na-SSZ-13 molecular sieve with a core-shell structure is obtained, with a core-phase silicon-aluminum ratio of 8 and a shell-phase silicon-aluminum ratio of 17.
[0032] 10 g of the calcined Na-SSZ-13@Na-SSZ-13 molecular sieve with a core-shell structure was added to 100 ml of 0.5 mol / L ammonium sulfate solution, and stirred continuously at 80°C for 6 h. After cooling, it was filtered and washed thoroughly, and then the exchange was repeated three times. It was filtered and washed thoroughly, and finally calcined at 550°C for 6 h to obtain a hydrogen-type core-shell structure H-SSZ-13@H-SSZ-13 molecular sieve. Finally, the obtained H-SSZ-13@H-SSZ-13 molecular sieve was added to 47.2 ml of 0.1 mol / L copper acetate solution and stirred continuously at 80°C for 6 hours. After the exchange was completed, the temperature was lowered. The product was filtered and washed thoroughly, dried in a 100°C oven for 8 hours, and then calcined in a 600°C muffle furnace for 6 hours to obtain a Cu-SSZ-13@Cu-SSZ-13 molecular sieve with a Cu loading of 4 wt% and a silicon-aluminum ratio of 8 as the core phase and a Cu-SSZ-13 molecular sieve with a Cu loading of 2 wt% and a silicon-aluminum ratio of 17 as the shell phase.
[0033] Example 2
[0034] A novel core-shell denitration catalyst, comprising a Cu-SSZ-13 molecular sieve with a Cu loading of 4.3wt% and a silicon-aluminum ratio of 6 as a core phase, and a Cu-SSZ-13 molecular sieve with a Cu loading of 2.3wt% and a silicon-aluminum ratio of 15 as a shell phase, namely, Cu-SSZ-13@Cu-SSZ-13 molecular sieve.
[0035] The synthesis method of the novel core-shell denitration catalyst is as follows:
[0036] Mix 6.603g KOH and 15g deionized water, put them into a crystallization kettle, stir at 80 rpm at room temperature to obtain a clear solution, then add 30ml water glass with a modulus of 3.2 (containing 35.84% SiO2 and 11.2wt% Na2O), 7.5ml TMAdaOH aqueous solution with a mass fraction of 25wt% and 60g deionized water, and finally add 6.0g NaY molecular sieve. Seal the kettle, heat to 150℃, and continue stirring for crystallization for 8h. After the reaction is completed, cool down and release the pressure. After filtering and washing the product, place it in a 120℃ oven to dry for 6h, and then roast it in a 550℃ muffle furnace for 8h. Finally, Na-SSZ-13 with a SiO2 / Al2O3 ratio of 6 is obtained.
[0037] Add 30.0ml silica sol (containing 30.1% SiO2), 1.03g KOH, 10.86g aluminum sulfate (containing 15.9wt% Al2O3), 4.1g TMAdaOH, 8.0g Na-SSZ-13 with a SiO2 / Al2O3 ratio of 6 synthesized in the previous step and 40g deionized water in turn. Seal the kettle, heat to 160°C, and stir continuously for 24h. After the reaction is completed, cool down and release the pressure. After filtering and washing the product, place it in a 100°C oven to dry for 8h, and then roast it in a 600°C muffle furnace for 6h. Finally, Na-SSZ-13@Na-SSZ-13 molecular sieve with a core-shell structure is obtained, with a core-phase silicon-aluminum ratio of 6 and a shell-phase silicon-aluminum ratio of 15.
[0038] 10 g of calcined Na-SSZ-13@Na-SSZ-13 molecular sieve with a core-shell structure was added to 100 ml of 0.5 mol / L ammonium sulfate solution, stirred continuously at 80°C for 6 h, filtered and washed thoroughly after cooling, then exchanged three times, filtered and washed thoroughly, and finally calcined at 550°C for 6 h to obtain a hydrogen-type H-SSZ-13@H-SSZ-13 core-shell structure molecular sieve. Finally, the obtained H-SSZ-13@H-SSZ-13 core-shell structure molecular sieve was added to 51 ml of 0.1 mol / L copper acetate solution and stirred continuously at 80°C for 6 hours. After the exchange was completed, the temperature was lowered. The product was filtered and washed thoroughly, dried in a 100°C oven for 8 hours, and then calcined in a 600°C muffle furnace for 6 hours to obtain a Cu-SSZ-13@Cu-SSZ-13 molecular sieve with a Cu loading of 4.3wt% and a silicon-aluminum ratio of 6 as the core phase and a Cu-SSZ-13 molecular sieve with a Cu loading of 2.3wt% and a silicon-aluminum ratio of 15 as the shell phase.
[0039] Example 3
[0040] Mix 4.428g NaOH and 10g deionized water, put them into a crystallization kettle, stir at 80 rpm at room temperature to obtain a clear solution, then add 30ml water glass with a modulus of 2.8 (containing 27.21% SiO2 and 9.17wt% Na2O), 5.4ml TMAdaOH (25% aqueous solution) and 71g deionized water, and finally add 7.5g NaY molecular sieve. Seal the kettle, heat to 140℃, and continue stirring for crystallization for 20h. After the reaction is completed, cool down and release the pressure. After filtering and washing the product, place it in a 120℃ oven to dry for 6h, and then roast it in a 550℃ muffle furnace for 8h. Finally, Na-SSZ-13 with a SiO2 / Al2O3 ratio of 4 is obtained.
[0041] 26.80ml silica sol (containing 30.1% SiO2), 1.12g alkali (NaOH), 10.86g aluminum sulfate (containing 15.9wt% Al2O3), 4.5g TMAdaOH, 7.0g Na-SSZ-13 with a SiO2 / Al2O3 ratio of 4 synthesized in the previous step and 50g deionized water were added in sequence. Seal the kettle, heat to 160°C, and stir continuously for 24h. After the reaction is completed, cool down and release the pressure. After filtering and washing the product, place it in a 100°C oven to dry for 8h, and then roast it in a 600°C muffle furnace for 6h. Finally, Na-SSZ-13@Na-SSZ-13 molecular sieve with a core-shell structure is obtained, with a core silicon-aluminum ratio of 4 and a shell silicon-aluminum ratio of 13.
[0042] 10g of calcined Na-SSZ-13@Na-SSZ-13 molecular sieve with core-shell structure was added to 100ml of ammonium sulfate solution with a concentration of 0.5mol / L, stirred continuously at 80℃ for 6h, filtered and washed fully after cooling, then exchanged three times, filtered and washed fully, and finally calcined at 550℃ for 6h to obtain hydrogen-type H-SSZ-13@H-SSZ-13 core-shell molecular sieve. Finally, the obtained H-SSZ-13@H-SSZ-13 core-shell molecular sieve was added to 55ml of copper acetate solution with a concentration of 0.1mol / L, stirred continuously at 80℃ for 6h, cooled, filtered, washed fully, placed in a 100℃ oven to dry for 8h, and then calcined in a muffle furnace at 600℃ for 6h, finally obtaining copper-based Cu-SSZ-13@Cu-SSZ-13 core-shell molecular sieves with different copper loadings. The core has a silicon-to-aluminum ratio of 6 and a copper loading of 4.5%, while the shell has a silicon-to-aluminum ratio of 13 and a copper loading of 2.6%.
[0043] Example 4
[0044] 6.235g of alkali and 13g of deionized water were mixed and put into a crystallization kettle. The mixture was stirred at 80 rpm at room temperature to obtain a clear solution. Then 25ml of water glass (containing 27.21% SiO2 and 9.17wt% Na2O) with a modulus of 2.8, 5.4ml of TMAdaOH (25% aqueous solution) and 55g of deionized water were added in sequence, and finally 6.1g of NaY molecular sieve was added. The kettle was sealed, heated to 140°C, and stirred for crystallization for 12h. After the reaction was completed, the temperature was lowered and the pressure was released. The product was filtered and fully washed, and then placed in a 120°C oven for drying for 6h, and then calcined in a 550°C muffle furnace for 8h. Finally, Na-SSZ-13 with a SiO2 / Al2O3 ratio of 9 was obtained.
[0045] Add 26.80ml silica sol (containing 30.1% SiO2), 1.12g alkali (NaOH), 10.86g aluminum sulfate (containing 15.9wt% Al2O3), 4.5g TMAdaOH, 7.0g Na-SSZ-13 with a SiO2 / Al2O3 ratio of 9 synthesized in the previous step and 50g deionized water in turn. Seal the kettle, heat to 160°C, and stir continuously for 24h. After the reaction is completed, cool down and release the pressure. After filtering and washing the product, place it in a 100°C oven to dry for 8h, and then roast it in a 600°C muffle furnace for 6h. Finally, Na-SSZ-13@Na-SSZ-13 molecular sieve with a core-shell structure is obtained, with a core silicon-aluminum ratio of 4 and a shell silicon-aluminum ratio of 13.
[0046] 10g of calcined Na-SSZ-13@Na-SSZ-13 molecular sieve with core-shell structure was added to 100ml of ammonium sulfate solution with a concentration of 0.5mol / L, stirred continuously at 80℃ for 6h, filtered and washed fully after cooling, then exchanged three times, filtered and washed fully, and finally calcined at 550℃ for 6h to obtain hydrogen-type H-SSZ-13@H-SSZ-13 core-shell molecular sieve. Finally, the obtained H-SSZ-13@H-SSZ-13 core-shell molecular sieve was added to 47.2ml of copper acetate solution with a concentration of 0.1mol / L, stirred continuously at 80℃ for 6h, cooled, filtered, washed fully, placed in a 100℃ oven to dry for 8h, and then calcined in a muffle furnace at 600℃ for 6h, finally obtaining copper-based Cu-SSZ-13@Cu-SSZ-13 core-shell molecular sieves with different copper loadings. The core has a silicon-to-aluminum ratio of 9 and a copper loading of 4.0%, while the shell has a silicon-to-aluminum ratio of 13 and a copper loading of 2.6%.
[0047] Comparative Example 1
[0048] A single silicon-aluminum ratio denitration catalyst is prepared, using a Cu-SSZ-13 molecular sieve catalyst with a Cu loading of 3.8wt% and a silicon-aluminum ratio of 8.
[0049] The synthesis method of the Cu-SSZ-13 denitration catalyst with a single silicon-aluminum ratio is as follows:
[0050] 5.1102g NaOH and 22g deionized water were mixed and put into a crystallization kettle. The mixture was stirred at 60 rpm at room temperature to obtain a clear solution. Then 31.5ml water glass with a modulus of 3.0 (containing 28.5% SiO2 and 9.5wt% Na2O), 8.1ml TMAdaOH aqueous solution with a mass fraction of 25wt% and 48g deionized water were added in sequence, and finally 4.5g NaY molecular sieve was added. The kettle was sealed, heated to 140°C, and stirred for crystallization for 24h. After the reaction was completed, the temperature was lowered and the pressure was released. The product was filtered and fully washed, and then placed in a 120°C oven for drying for 8h, and then calcined in a 600°C muffle furnace for 8h. Finally, Na-SSZ-13 with a SiO2 / Al2O3 ratio of 8.2 was obtained (actual test results of ICP test).
[0051] 20.0g of calcined Na-SSZ-13 molecular sieve with a single silicon-aluminum ratio of 8.2 was added to 200ml of 0.5mol / L ammonium sulfate solution, stirred continuously for 6h at 80℃, filtered and washed after cooling, and then the filter cake was added to 200ml of 0.5mol / L ammonium sulfate solution, exchanged three times, filtered, washed thoroughly, and finally calcined at 550℃ for 8h to obtain hydrogen-type H-SSZ-13 molecular sieve. Finally, H-SSZ-13 molecular sieve was added to 47.2ml of 0.1mol / L copper acetate solution, stirred continuously for 6h at 80℃, cooled after the exchange, filtered, washed thoroughly, placed in a 100℃ oven for 8h, and then calcined in a 600℃ muffle furnace for 6h to obtain a Cu-SSZ-13 molecular sieve catalyst with a Cu loading of 3.8wt% and a silicon-aluminum ratio of 7.8.
[0052] Comparative Example 2
[0053] A single silicon-aluminum ratio denitration catalyst is prepared, using a Cu-SSZ-13 molecular sieve catalyst with a Cu loading of 2.2wt% and a silicon-aluminum ratio of 16.
[0054] The synthesis method of the Cu-SSZ-13 denitration catalyst with a single silicon-aluminum ratio is as follows:
[0055] 31.1 ml silica sol (containing 30.1% SiO2), 1.1 g NaOH, 11.3 g aluminum sulfate (containing 15.9 wt% Al2O3), 5.0 g TMAdaOH and 40 g deionized water were added in sequence and mixed. The kettle was sealed, heated to 160°C, and stirred for 24 hours. After the reaction was completed, the temperature was lowered and the pressure was released. The product was filtered and washed thoroughly, and then placed in a 120°C oven to dry for 8 hours, and then calcined in a 600°C muffle furnace for 8 hours. Finally, Na-SSZ-13 molecular sieve with a single silicon-aluminum ratio of 16.3 (actual test result of ICP test) was obtained.
[0056] 20.0g of calcined Na-SSZ-13 molecular sieve with a single silicon-aluminum ratio of 16.3 was added to 200ml of ammonium sulfate solution with a concentration of 0.5mol / L, stirred continuously for 6h at 80℃, filtered and washed after cooling, and then the filter cake was added to 200ml of ammonium sulfate solution with a concentration of 0.5mol / L, exchanged three times, filtered, fully washed, and finally calcined at 550℃ for 8h to obtain hydrogen-type H-SSZ-13 molecular sieve. Finally, the obtained H-SSZ-13 molecular sieve was added to 47.2ml of copper acetate solution with a concentration of 0.05mol / L, stirred continuously for 6h at a temperature of 80℃, cooled after the exchange, filtered, fully washed, placed in a 100℃ oven to dry for 8h, and then calcined in a 600℃ muffle furnace for 6h to obtain a Cu-SSZ-13 molecular sieve catalyst with a Cu loading of 2.2wt% and a single silicon-aluminum ratio of 16.
[0057] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A novel core-shell denitration catalyst, characterized in that: The novel core-shell denitration catalyst is a Cu-SSZ-13@Cu-SSZ-13 molecular sieve with a Cu loading of 3.5wt%-4.5wt% and a silicon-aluminum ratio of 4-10 as a core phase and a Cu-SSZ-13 molecular sieve with a Cu loading of 1.5wt%-3.0wt% and a silicon-aluminum ratio of 13-17 as a shell phase.
2. A method for synthesizing a novel core-shell denitration catalyst, characterized in that: The method comprises the following steps: preparing a Na-SSZ-13@Na-SSZ-13 molecular sieve by an ion exchange method, wherein the Na-SSZ-13@Na-SSZ-13 molecular sieve is a core-shell structure, the silicon-aluminum ratio of the core phase is 4-10, and the silicon-aluminum ratio of the shell phase is 13-17.
3. The method for synthesizing the novel core-shell denitration catalyst according to claim 2, characterized in that: The specific process of the ion exchange is: adding Na-SSZ-13@Na-SSZ-13 molecular sieve to ammonium sulfate solution for ion exchange to obtain H-SSZ-13@H-SSZ-13 molecular sieve; then placing the H-SSZ-13@H-SSZ-13 molecular sieve in a cupric acetate solution for ion exchange to obtain Cu-SSZ-13@Cu-SSZ-13 molecular sieve; the mass volume ratio (g / mL) of the Na-SSZ-13@Na-SSZ-13 molecular sieve to the ammonium sulfate solution and the cupric acetate solution is 1:5-15:3-8; preferably, the concentration of the ammonium sulfate solution is 0.4-0.6 mol / L; the concentration of the cupric acetate solution is 0.1-0.3 mol / L.
4. The method for synthesizing the novel core-shell denitration catalyst according to claim 3, characterized in that: The temperature for ion exchange in ammonium sulfate solution is 75-85°C, the exchange time is 5-7h, and the number of exchanges is 3-4 times; the temperature for ion exchange in copper acetate solution is 75-85°C, and the exchange time is 5-7h.
5. The method for synthesizing the novel core-shell denitration catalyst according to any one of claims 2 to 4, characterized in that: The synthesis method of the Na-SSZ-13@Na-SSZ-13 molecular sieve is as follows: (1) using a crystal rotation method to synthesize a core phase Na-SSZ-13 molecular sieve with a silicon-aluminum ratio of 4-10; (2) adding the core phase Na-SSZ-13 molecular sieve to the initial mother liquor of SSZ-13 molecular sieve synthesis, stirring, and crystallizing to generate a shell phase Na-SSZ-13 molecular sieve with a silicon-aluminum ratio of 13-17 on the core phase Na-SSZ-13 molecular sieve.
6. The method for synthesizing the novel core-shell denitration catalyst according to claim 5, characterized in that: The specific process of step (1) is: mixing an alkali source, a silicon source, water, a template, and an aluminum source in a molar ratio of 0.1-0.3:1:5.0-15.0:0.01-0.05:0.02-0.08, and stirring evenly to obtain an initial gel; placing the initial gel in a high-temperature reaction kettle, crystallizing at 120-160°C for 8-24 hours, cooling, separating, drying, and calcining to obtain a core phase Na-SSZ-13 molecular sieve with a silicon-aluminum ratio of 4-10; preferably, the crystallization reaction temperature is 140-160°C; preferably, the crystallization reaction time is 12-18 hours.
7. The method for synthesizing the novel core-shell denitration catalyst according to claim 6, characterized in that: In the step (1), the alkali source is selected from NaOH or KOH; the silicon source is selected from one or a combination of water glass, tetraethyl orthosilicate, silica sol, fumed silica, sodium silicate; the template agent is N,N,N-trimethyl-1-adamantanammonium hydroxide; and the aluminum source is Y molecular sieve.
8. The method for synthesizing the novel core-shell denitration catalyst according to claim 7, characterized in that: The Y molecular sieve is selected from one or a combination of NaY, NH4Y, and HY; the silicon-aluminum ratio of the Y molecular sieve is 1-20; preferably, the Y molecular sieve is NaY; preferably, the silicon-aluminum ratio of the Y molecular sieve is 2-10; more preferably, it is 5-7.
9. The method for synthesizing the novel core-shell denitration catalyst according to any one of claims 5 to 8, characterized in that: The specific process of step (2) is: mixing the initial mother liquid for synthesizing SSZ-13 molecular sieve composed of alkali source, silicon source, water, template agent and aluminum source in a molar ratio of 0.05-0.1:1:8.0-20.0:0.01-0.05:0.05-0.1 with the core phase Na-SSZ-13 molecular sieve with a silicon-aluminum ratio of 4-10 obtained in step (1), stirring, crystallizing at 150-170° C. for 18-26 hours, cooling, separating, drying and calcining to obtain Na-SSZ-13@Na-SSZ-13 molecular sieve; Preferably, the alkali source is selected from NaOH or KOH; the silicon source is selected from one or a combination of tetraethyl orthosilicate, silica sol, fumed silica, sodium silicate; the template is N,N,N-trimethyl-1-adamantanammonium hydroxide; and the aluminum source is aluminum sulfate.
10. Use of the novel core-shell denitration catalyst according to claim 1 or the novel core-shell denitration catalyst obtained by the synthesis method according to any one of claims 2 to 9 as an NH3-SCR catalyst, characterized in that: The reaction temperature is controlled at 120°C-650°C, ammonia is used as the reducing agent, the total gas flow rate is controlled to be 500ml / min, and the space velocity is controlled to be 80000-200000 / h; preferably, the catalyst is first subjected to hydrothermal aging treatment and then used for catalytic reduction of NOx, and the treatment conditions are: at 850°C, treated in air containing 10% water vapor for 16 hours.
Citation Information
Cited By
Core-shell structure copper-based catalyst as well as preparation method and application thereof
CN120754866A
Core-shell structure cobalt-based catalyst as well as preparation method and application thereof
CN120754867A